PENINGKATAN KEMAMPUAN BERHITUNG PERMULAAN MELALUI PERMAINAN CONGKLAK PADA ANAK USIA 5-6 TAHUN DI TK PAUD TERPADU PONTIANAK - Ulansari, Evi; Halida, Halida; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to determine the improvement of early numeracy skills through Congklak games in children aged 5-6 years in Pontianak Integrated PAUD Kindergarten. The research method used is the action method. The form of this research is collaborative Classroom Action Research. The research subjects were 22 children aged 5-6 years and 1 class B3 teacher. Data collection techniques in this study were planning, observation, interviews, and documentation techniques. The results of the study showed an increase in early numeracy skills through congklak games as many as 64% of children reached the very well developed category in calculating numbers 1-20, 55% in adding numbers 1-20, and 50% in subtracting numbers 1-20. Based on the results of the study, it can be concluded that congklak games can be a medium in improving early numeracy skills in class B3 children in Pontianak Integrated PAUD Kindergarten. This is demonstrated by the improvement in children's ability to count from 1-20, add, and subtract numbers, using a cyclical approach through planning, implementation, and evaluation. This research is expected to lead to the implementation of learning using the congklak game to improve early counting skills in early childhood.